Taxonomia de Poptella compressa e P. Paraguayensis (Characiformes: Characidae: Stethaprioninae) através da morfometria geométrica - Câmara, Anna Luiza Nardi [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Recently, the subfamily Stethaprioninae was redefined by changing its size to encompass several genera of characin fishes now grouped into four tribes. Regarding the tribe Stethaprionini, the "clade Stethaprion" refers to the original composition of the subfamily Stethaprioninae, a monophyletic group formed by the genera Stethaprion, Brachychalcinus, Poptella and Orthospinus. This clade is diagnosed as distinct from the other characins by the presence of a predorsal spine articulated with the first ray of the dorsal fin. In addition, the shape of the predorsal spine is the condition used for the definition and identification of the previous genera. listed. The genus Poptella is the most diverse of the group and also the most complex. taxonomically, with seven valid species. In recent decades, some populations have been collected and identified as Poptella compressa, they had different degrees of chromatophore distribution along the adipose fin, leading to confusion with Poptella paraguayensis, but differences were observed in the shape of the predorsal spines of these populations, which could be indicative of greater diversity. In this way, the present work used Geometric Morphometry to analyze and compare the shape of the predorsal spine of the different populations. Our results indicate that of the 11 populations analyzed, nine showed significant differences between them, indicating that the shape of this structure can be used as a reliable source of diagnosis in species of this genus.
Taxonomía de Poptella compressa y P. Paraguayensis (Characiformes: Characidae: Stethaprioninae) mediante morfometría geométrica
Keywords: Taxonomia; Biodiversidade; Ictiologia; Morfometria; Sistemática